1999
DOI: 10.2307/2667031
|View full text |Cite
|
Sign up to set email alerts
|

The Time Famine: Toward a Sociology of Work Time

Abstract: and three anonymous reviewers offered invaluable advice and suggestions.This paper describes a qualitative study of how people use their time at work, why they use it this way, and whether their way of using time is optimal for them or their work groups. Results of a nine-month field study of the work practices of a software engineering team revealed that the group's collective use of time perpetuated its members' "time famine," a feeling of having too much to do and not enough time to do it. Engineers had dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
552
5
28

Year Published

2000
2000
2015
2015

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 749 publications
(618 citation statements)
references
References 14 publications
(2 reference statements)
15
552
5
28
Order By: Relevance
“…Slack time, defined as the amount of time and attention the team members can potentially commit to the project beyond the minimum required, is a specific form of slack that can affect performance as well as satisfaction in organizations. For example, Perlow (1999) found that "time famine", a feeling of having too much to do and not enough time to do it, affected how software engineers used their time at work and reduced their productivity. Also, interventions that increase or decrease slack time can influence the performance of knowledge-intensive work.…”
Section: Capability-enhancing Team Conditionsmentioning
confidence: 99%
“…Slack time, defined as the amount of time and attention the team members can potentially commit to the project beyond the minimum required, is a specific form of slack that can affect performance as well as satisfaction in organizations. For example, Perlow (1999) found that "time famine", a feeling of having too much to do and not enough time to do it, affected how software engineers used their time at work and reduced their productivity. Also, interventions that increase or decrease slack time can influence the performance of knowledge-intensive work.…”
Section: Capability-enhancing Team Conditionsmentioning
confidence: 99%
“…Spontaneous, informal communication at work is important, yet, it often helps the initiator of the communication at the expense of the person being interrupted (Perlow, 1999 ). Interventions designed to balance the benefi ts and costs of spontaneous communication have often had unforeseen consequences.…”
Section: Modeling For the Research Questionmentioning
confidence: 99%
“…The communication also helps with identifying prospects [Ebling, 2001], sales and relationship building [Ginovsky, 2001], and deepening customer loyalty [Kranzley, 2001]. Perlow [1999] describes a software company characterized by an environment. It also allows for easy follow-up on customers' needs [Marks, 1998].…”
Section: Literature Reviewmentioning
confidence: 99%